Effect of profitability, liquidity, and company size on capital structure: Evidence from Indonesia manufacturing companies - Yohanes Suhardjo; Abdul Karim; Mohamad Sigit Taruna (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
This study aims to see the effect of profitability,liquidity, and company size on the capital structure of the manufacturing companies listed on the Indonesian Stock Exchange in 2018-2020. Secondary data is used for the research and it is collected using purposive sampling. The data then analyzed using multiple linear regression. Research results shows that profitability and companies size have no effect on capital structure. Meanwhile, the liquidity have effect on capital structure. The limitation of this study is the lack of a research period to the small sample used. Researcher’s suggestion for further research is to increase the time period of the study, which is aimed to increase the accuracy of the research data.